Cancer free survival in mutation positive HNPCC individuals with colorectal adenomatous polyps identified on surveillance colonoscopy - Swart, Oostewalt (Adolescent Health Research Institute, 2024)
The prevalence of colorectal cancer (CRC) places it in the top five cancers worldwide and is the second most common cause of cancer related death. Developed populations have a 5-6% lifetime risk of CRC(l). The South African Cancer Registry (last updated 2004) shows a 1/98 and 1/150 life time risk for developing CRC in males and females respectively (2).